United Arab Emirates : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the United Arab Emirates. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that non-oil economic activity in the United Arab Emirates slowed to 3.7 percent in 2015. Negative effects on overall growth were partially offset by the increase in oil production. Despite the strong fiscal policy response to adjust to lower oil prices, the fiscal balance turned to a deficit of 2.1 percent of GDP, while the current account surplus declined to 3.3 percent of GDP. Banks remained well capitalized and liquid, though pressures on profitability are emerging as asset quality weakens owing to the economic slowdown and rising funding costs. Economic activity is expected to moderate further in 2016, before improving over the medium term.